Предмет: Математика,
автор: midwet
∫(arctansqrt(x)/(sqrt(x)*(1+x)))dx
Ответы
Автор ответа:
0
Замена переменной (arctg√x) = y - >
1/((1+x)*2√x)dx = dy т.к. (arctgx) ' = 1/(1+x^2)
-> dx = dy*(2√x)*(1+x) -> ∫ ( ) dx =
= ∫ (y/((√x)*(1+x))*dy*(1+x)*2√x) = ∫ 2ydy = y^2 + C =
(arctg√x)^2 + C
1/((1+x)*2√x)dx = dy т.к. (arctgx) ' = 1/(1+x^2)
-> dx = dy*(2√x)*(1+x) -> ∫ ( ) dx =
= ∫ (y/((√x)*(1+x))*dy*(1+x)*2√x) = ∫ 2ydy = y^2 + C =
(arctg√x)^2 + C
Похожие вопросы
Предмет: Биология,
автор: mikaanastaseeva12
Предмет: Математика,
автор: shaganovakate093
Предмет: Алгебра,
автор: kotsuslov777
Предмет: История,
автор: Настенка77